Implementation of Lean Manufacturing with VSM method for Increase TestingProcess Efficiency Laboratory Drug Antacid - SUHAERI, SUHAERI; Mayanti, Malinda Mayanti; Ikatrinasari, Zulfa Fitri Ikatrinasari (JURNAL TEKNIK INDUSTRI, 2024)
According to the World Health Organization (WHO), 15 – 30% of the world's population suffers fromdigestive tract diseases every year, and Indonesia ranks third with the most cases. This tragedyprompted the pharmaceutical industry to maximize production of antacid drugs. One of them isspeeding up the analysis process for antacid medications without compromising the accuracy of theanalysis results. This research aims to increase productivity by identifying waste activities, makingimprovements using a lean approach, and adopting I4.0. The research results stated that the mainwaste occurred in an ineffective process, namely the titrant solution standardization process and notutilizing resources with automation technology. After the future state value stream mapping wasdesigned, the total lead time decreased from 35,760 seconds to 26,940 seconds and the total distancefrom 225 meters to 115 meters, so with the proposed improvements, there was an increase inprocess cycle efficiency (PCE) from 36.07% to 42.87%.